The Governance of Energy in China - Andrews-Speed, P. author. aut Link
XVI, 259 p.
Keywords: The way in which energy is governed in China is driving its rising level of carbon dioxide emissions. This book analyses the nature of energy governance in China by combining ideas relating to transition management with institutionalist theories, which helps to identify factors which assist or constrain the country's path to a low-carbon economy.